Evidence for evolved Hadean crust from Sr isotopes in apatite within Eoarchean zircon from the Acasta Gneiss Complex. (15th August 2018) - Emo, Robert B.; Smit, Matthijs A.; Schmitt, Melanie; Kooijman, Ellen; Scherer, Erik E.; Sprung, Peter; Bleeker, Wouter; Mezger, Klaus
Abstract: Current models for the properties of Hadean-Eoarchean crust encompass a full range of possibilities, involving crust that is anywhere from thick and differentiated to thin and mafic. New data are needed to test and refine these models, and, ultimately, to determine how continents were first formed. The Rb-Sr system provides a potentially powerful proxy for crustal evolution and composition. However, this system has thus far been underutilized in studies on early crustal evolution due to its susceptibility to re-equilibration. Overcoming this issue requires new analytical approaches to micro-sample ancient Sr-rich mineral relics that may retain primary Rb-Sr systematics, allowing for the precise and accurate determination of initial 87 Sr/ 86 Sr values. In this study, we used a novel application of laser-ablation multi-collector inductively coupled plasma mass spectrometry to determine the Sr isotope composition of apatite inclusions in >3.6 Ga zircon grains from Eoarchean granodiorite gneisses of the Acasta Gneiss Complex, Slave Province, Canada. The 87 Rb-corrected 87 Sr/ 86 Sr values of these inclusions are largely identical and are distinctly different from values obtained from altered matrix apatite. The inclusion data provide the first direct estimate of initial 87 Sr/ 86 Sr for these ancient rocks. Combining this result with information on the protolith and source-extraction age yields estimates for the range of Rb/Sr values, and by extension composition, that the source of these rocks may have had. The data indicate that continental crust containing over 60 wt% of SiO2 was present in the ca. 4.2 Ga source of the Acasta Gneiss Complex. Thus vestiges of evolved crust must have existed within the primitive proto-continents that were present on the Hadean Earth.